Analisis Kualitas Sifat Fisik Kertas Dengan Penambahan Kalsium Silikat Pada Kertas Mengandung Filler PCC & GCC - Gabriella Carissa Putihardjo; Zulfansyah Zulfansyah; Hari Rionaldo; Janso Hasudungan (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Filler is one of paper component inside paper made in paper industry and nominated as number two biggest component in paper. In order to reduce over basis weight problem in one of paper industry, a research about filler modification using calcium silicate is held. The purpose of the research is to observe the effect of calcium silicate addition and it’s optimum dosage in paper making process. Lab trial showing that adding the calcium silicate on 70 gsm copy and offset paper making process show that even with filler content increment, calcium silicate help to maintain paper grammage and thickness. Where for the copy paper paper thickness at filler 23% without calcium cilicate addition is 123 mm and with addition of calcium cilicate 1% dan 2% dosage, paper thickness become 129 mm. For offset paper paper thickness at filler 23% without calcium cilicate addition is 123 mm and with addition of calcium cilicate 1% dan 2% dosage, paper thickness become 124 mm.Keywords: Paper Making, Filler, PCC, GCC, Calcium Silicate, Paper Thickness.